Indonesia Literature in Translation (Indonesia and Japanese Translation Context) - Lina Rosliana (IZUMI, 2024)
Indonesia has rich literature that is not widely known outside the country's borders. Translating Indonesian literary works can be the key to experiencing its literary richness and knowing its social, cultural, or political reality. There have been many studies on translating Japanese or English literature into Indonesian, but not vice versa. This study can play a role in formulating strategies for translating Indonesian literary works into foreign languages and, at the same time, become a contribution to introduce Indonesian literature through translation studies. The research questions proposed align with the study's primary objective of issues in translation; How is the passage of Indonesian literature in translation? Literary research with qualitative approaches will be conducted in this study. The stages are divided into three steps, i.e., 1) Data collection, 2) Data analysis, and 3) Data presentation. Before independence, Japan established an institution in Indonesia whose job was to translate literary works, either in book form or published in magazines and newspapers for the Indonesian people. However, in practice, this was done to control the reading of the Indonesian people and for propaganda purposes. Thus, the literary works circulated and translated supported colonial projects. After independence, the Japanese grant program for translating Southeast Asian literary works has also significantly impacted the number of Indonesian literary works translated into Japanese. However, these translated works have yet to reach the Japanese public and are mostly accessed by a limited circle of Indonesian observers in Japan.  gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor